2019
DOI: 10.1002/jmri.26916
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial velocity, intra‐, and interventricular dyssynchrony evaluated by tissue phase mapping in pediatric heart transplant recipients

Abstract: Background Endomyocardial biopsy (EMB) is the standard method for detecting allograft rejection in pediatric heart transplants (Htx). As EMB is invasive and carries a risk of complications, there is a need for a noninvasive alternative for allograft monitoring. Purpose To quantify left and right ventricular (LV & RV) peak velocities, velocity twist, and intra‐/interventricular dyssynchrony using tissue phase mapping (TPM) in pediatric Htx compared with controls, and to explore the relationship between global c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In recent years, CMR has shown substantial promise for detection of graft dysfunction in adult heart transplant recipients [ 21 , 23 , 24 , 28 , 37 , 49 53 ], however, data are quite limited in PHT [ 37 , 38 , 40 , 43 , 54 , 55 ]. Our study demonstrates the safety and feasibility of comprehensive CMR with regadenoson stress perfusion for graft surveillance in PHT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, CMR has shown substantial promise for detection of graft dysfunction in adult heart transplant recipients [ 21 , 23 , 24 , 28 , 37 , 49 53 ], however, data are quite limited in PHT [ 37 , 38 , 40 , 43 , 54 , 55 ]. Our study demonstrates the safety and feasibility of comprehensive CMR with regadenoson stress perfusion for graft surveillance in PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography-derived strain and CMR derived myocardial velocities are often abnormal during an acute rejection episode or with cumulative history of repetitive rejections [ 11 13 , 28 , 37 , 37 , 40 , 41 , 62 , 63 ]. Miller et al [ 30 ] have reported an association of reduced GCS by CMR tagging with clinically significant ACR (grade 2 R or higher) in adult heart transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMR has the ability to non-invasively characterize intramyocardial function using techniques such as myocardial tagging, 4,5 strain-encoded (SENC) imaging, 6 cine displacement-encoded imaging with stimulated echoes (DENSE), 7,8 and tissue phase mapping (TPM). 9,10 These techniques have proven useful in diagnosing and monitoring abnormal myocardial function in a wide range of cardiovascular conditions including congenital heart diseases, 11,12 cardiotoxicities, 13,14 cardiac transplantation, [15][16][17] left ventricular dyssynchrony, 18,19 and various cardiomyopathies. [20][21][22] In this study, we will focus on TPM, which is a black-blood 2D cine phase contrast MRI pulse sequence with three-directional tissue velocity encoding for quantification of regional biventricular myocardial velocities.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recently, several studies have demonstrated significant differences in biventricular global and regional velocities in heart transplant (HTx) patients (adult and pediatric) with and without transplant rejection. 15,16 Despite these studies demonstrating feasibility, the clinical translation of TPM is hampered by the requisite labor-intensive manual segmentation of the myocardial contours for all cardiac frames. In general, manual segmentation of TPM images is more challenging for the RV than the LV, because the former has a thinner wall, highly trabeculated myocardium, and epicardial fat partially superimposed on the myocardial wall.…”
Section: Introductionmentioning
confidence: 99%